Analisa Runoff Pada Sub DAS Lematang Hulu - Gina Putri Verrina; Dinar Dwi Anugerah; Helmi Haki (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2013)
Runoff is one of the factors that can cause landslides. This phenomenon occurs in Lematang watershed especially in upstream region. The purpose of this research is to determine runoff that occur in LematangHulu sub-watershed. In the analysis of runoff, LematangHulu watershed was divided into 5 sub-watershed, namely Sub DAS L Hulu 1 – Sub DAS L Hulu 5. The method used in analyzing this runoff is Rational one. It considers runoff coefficient, the intensity of rainfall and catchment area. All parameters runoff’s calculation obtained by using spatial interpretation of satellite images for land use (C),boundary / area in the drainage (A) from analysis of DEM ( Digital Elevation Model ), and the distribution of rainfall intensity (I) using Algebra Average & Mononobe formula. The result show that in Sub DAS L Hulu 3, one of the sub-watershed should receives extra attention because it yields high runoff which is equal to 679,8 m3/s. It may cause flood or landslide in the future. Keywords: runoff, watershed, Rational